Why was Japan hit so hard by the global financial crisis? - Masahiro Kawai; Shinji Takagi (Asian Development Bank Institute (ADBI), 2009)
Japan was hit hard by the global financial crisis even though its relatively resilient financial system initially limited the direct impact. The severe collapse of industrial production that followed was no doubt attributable to a confluence of factors, but the paper highlights the impact that came from the contractionary effect of global deleveraging on the real economy. In this environment, Japan was particularly vulnerable because of the structural changes that had taken place over the past decade in its trade and industrial structures. Vector autoregression analysis confirms that, as a result of these structural changes, Japanese output became much more responsive to output shocks in the advanced markets of the United States and Western Europe. The structural changes had two components. First, over 90% of Japan's exports consisted of highly income-elastic industrial supplies, capital goods, and consumer durables. Though emerging Asia is Japan's largest export market, its imports from Japan largely consist of intermediate goods used in the production of final goods destined for the US and Western Europe. Second, Japan's trade dependence had increased since the early 2000s, as evidenced by a rising export to gross domestic product ratio and a declining share for the non-tradable sector. Though increasing trade openness is a natural part of economic globalization and regional integration, the manner in which this process had played out made Japan particularly vulnerable to a negative demand shock coming from outside. To make Japan more resilient to external shocks, policymakers could promote the export of finished goods to emerging Asia by establishing a region-wide free trade arrangement. To promote domestic demand, the social protection system needs to be strengthened so as to reduce households' uncertainty for the future; a more liberal immigration policy should help invigorate private investment in an aging society. To facilitate a better allocation of resources, further deregulatory measures in the more regulated non-tradable goods sector are called for; a substantial lifting of restrictions in agriculture, especially regarding the corporatization of production, would be especially helpful. With little available fiscal space, these measures will help create a climate in which private investment can flourish, driven by final domestic demand.
Keywords: F40; F41; 330